Flexible modelling of time-varying exposures and recurrent events to analyse training load effects in team sports injuries - Zumeta-Olaskoaga, Lore; Bender, Andreas; Lee, Dae Jin (Royal Statistical Society Oxford University Press, 2024)
We present a flexible modelling approach to analyse time-varying exposures and recurrent events in team sports injuries. The approach is based on the piece-wise exponential additive mixed model where the effects of past exposures (i.e. high-intensity training loads) may accumulate over time and present complex forms of association. In order to identify a relevant time window at which past exposures have an impact on the current risk, we propose a penalty approach. We conduct a simulation study to evaluate the performance of the proposed model, under different true weight functions and different levels of heterogeneity between recurrent events. Finally, we illustrate the approach with a case study application involving an elite male football team participating in the Spanish LaLiga competition. The cohort includes time-loss injuries and external training load variables tracked by Global Positioning System devices, during the seasons 2017–2018 and 2018–2019.
Keywords: 12 Matemáticas::1209 Estadística; ODS 5 - Igualdad de género; cumulative effect; football injuries; recurrent events; sports analytics; survival analysis; time-varying exposures